SIFAT FISIK, KIMIA, DAN TINGKAT KESUKAAN MI KERING YANG DISUBSTITUSI TEPUNG UWI UNGU (Discorea alata L.) - Andini, Ainun Noor; Tamaroh, Siti (Universitas Sebelas Maret (UNS), 2022)
Purple yam (Dioscorea alata L.) is a type of tuber that has the potential as a source of carbohydrates, and there are antioxidant compounds in the form of anthocyanins and phenolic compounds. The manufacture of dried noodles substituted with purple yam flour is expected to increase the utilization of purple yam and reduce the use of wheat flour as the main ingredient for making noodles. The addition of Carboxy Methyl Cellulose aims to improve the physical properties of dried noodles. In this study, the manufacture of dried noodles was carried out by treating the raw material with a ratio of wheat flour: purple yam flour 80:20, 70:30, 60:40 and CMC 0.25, 0.50, 0.75 g/100 g. The resulting dried noodles were tested for water content, ash content, protein content, anthocyanin content, total phenolic content, antioxidant activity, color, texture, cooking loss and preference test. The data obtained were then carried out with a one-way ANOVA statistical test and if there was a significant difference, it was continued with the DMRT test at a 5% confidence level. The results of this study indicate that the manufacture of dried noodles can be made with a ratio of wheat flour: purple yam flour ratio of 70:30, so as to reduce the use of wheat flour.In the manufacture of dried noodles with substitution 30 parts of purple yam flour used CMC 0.50 g/100 g. The characteristics of the best dry noodles produced in this study were as follows : water content 10.24% wb, protein content 12.19% db, ash content 3.97% db, anthocyanins content 4.93 mg/100 g db, total phenolic content 19.48 g GAE/ 100 g db, antioxidant activity 3.14%, color L= 29.53, a*=6.80, b*=7.58, cooking loss = 8.52% and overall preference level cooked dried noodle = 3.80 (preferred).